Determinasi Ketahanan Pangan: Studi Kasus 10 Provinsi di Pulau Sumatera - Lisa Eva Margaretha; Sucihatiningsih Dian Wisika Prajanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Food is one of the major challenges that plays a crucial role in meeting the consumption needs of the population as part of efforts to address food security conditions in a region. Uneven food availability and access across regions lead to economic instability and undermine food security. This study was conducted to examine the various factors influencing food security in 10 provinces on the island of Sumatra. The study employed a panel data regression analysis approach under classical assumptions, using the Ordinary Least Squares (OLS) method via E-views software version 13. The findings indicate that the number of workers in the agricultural sector, the availability of drinking water, harvested area, farmer welfare, and government budget implementation significantly influence food security in the 10 provinces of Sumatra from 2019 to 2023. Therefore, it is crucial for the government to implement more equitable policies to strengthen regional and even national food security. Strengthening community economic capacity through increased income and economic stability to achieve equitable food distribution will help maintain food security in each province on the island of Sumatra. Additionally, the need for sustained government investment in strategic food commodities will enhance food security in the provinces of Sumatra.